Education in Britain - British Information Service, New York, NY. Reference Div.; British Information Service, New York, NY. Reference Div. (London : Her Majesty's stationary office, 1958)
Intended for reference purposes, this pamphlet describes the state system of education and the general policy implemented in Britain, including England, Wales, Scotland, and Northern Ireland. Among notable features of the system are the large number of students participating, the freedom of teachers from official direction, the decentralization of administration, the prominent part played by voluntary agencies, the academic autonomy of the universities, and the system of financial support for students in higher education. Historical development and administration of the public system of primary, secondary, adult education, and higher education are fully described. Short sections are included on teachers and teaching aids, educational research, and educational building. Appendices include information on educational statistics and government departments and educational organisations. A bibliography of official publications, COI Reference material, and other publications is provided. (Author/SJM)
Includes index.
Microfiche.
Keywords: Educational Development; Great Britain